Answer: -74
Step-by-step explanation:
First you have to solve - 2y - 9 = 7 to find what "y" equals so we can plug that into 9y - 2
1. Solve -2y - 9 =7:
-2y = 16
y = -8
2. Plug -8 into the expression 9y - 2:
9(-8) - 2
-72 -2
-74!
Im sorry if i didnt do this correctly :/
Step-by-step explanation:
1/2x+2−1/6x=1/6x−1−1/6x
1/3x+2=−1
1/3x+2−2=−1−2
1/3x=−3
3*(1/3x)=(3)*(−3)
x=−9 <- ANSWER
Y=x-3
please can i have a brainliest
Answer:
0.18431525 = 18.4%
Step-by-step explanation:
General Formula :
total trials Cn⋅p(success)^n⋅p(fail)^total−n
1198144* (.0218)^3 * (1-.0218)^191